South African Police Services Officials` Perceptions of Community-Police Relations in Durban, South Africa - Dlamini, Siyanda (International Journal of Criminology and Sociology, 2021)
olice officers’ views about police-citizen relationships are shaped not only by opportunities to interact with community residents during normal police work but also in part by efforts due to the larger police mission of encouraging and supporting such attitudes. In recent years, police in different countries has shifted from the traditional reactive form of policing towards community-oriented approaches. Hence, the purpose of this paper is to explore police officers’ views of citizen-police relationships and community policing in Durban, South Africa. A qualitative research approach was adopted, to explore such perceptions in the study area. The findings collected through semi-structured interviews with the South African Police Services personnel suggested that police officer were dissatisfied and at best ambiguous about citizens’ participation in crime prevention activities or support for the police in a township dwelling. However, in a suburban area, the perceptions marked an improvement in their attitudes on various dimensions. These include officers’ views about the overall police mission, increased emphasis on service-oriented policing in contrast to a law enforcement approach, support for community policing, perceived citizens’ willingness to cooperate with the police in crime prevention activities, and decreased cynicism about citizens. These findings suggest confidence in the utility of community policing ideas.